Part-time Work, Wages and Productivity: Evidence from Belgian Matched Panel Data - Andrea Garnero; Stephan Kampelmann; Francois Rycx (Institute for the Study of Labor (IZA), 2013)
The authors use matched employer-employee panel data on Belgian private-sector firms to estimate the relationship between wage/productivity differentials and the firm's labor composition in terms of part-time and sex. Findings suggest that the groups of women and part-timers generate employer rents, but also that the origin of these rents differs (relatively lower wages for women, relatively higher productivity for part-timers). Interactions between gender and part-time suggest that the positive productivity effect is driven by male part-timers working more than 25 hours, whereas the share of female part-timers is associated with wage penalties. The authors conclude that men and women differ with respect to motives for reducing working hours and the types of part-time jobs available to them: women often have to accommodate domestic constraints by downgrading to more flexible jobs, whereas male part-time work is frequently related to training and collectively negotiated hours reductions that do not affect hourly pay.
Keywords: J22; J24; J31; 330; wages; productivity; part-time employment; gender; matched panel data; GMM